Bicycle helmet wearing is associated with closer overtaking by drivers: A response to Olivier and Walter, 2013. (February 2019) - Walker, Ian; Robinson, Dorothy L.
Highlights: UK drivers passed a bicyclist closer on average when the bicyclist wore a helmet. Passing distances decreased on average by 0.23 standard deviations with the helmet. The effect could vary slightly with the rider's road positioning. Abstract: There is a body of research on how driver behaviour might change in response to bicyclists' appearance. In 2007, Walker published a study suggesting motorists drove closer on average when passing a bicyclist if the rider wore a helmet, potentially increasing the risk of a collision. Olivier and Walter re-analysed the same data in 2013 and claimed helmet wearing was not associated with close vehicle passing. Here we show how Olivier and Walter's analysis addressed a subtly, but importantly, different question than Walker's. Their conclusion was based on omitting information about variability in driver behaviour and instead dividing overtakes into two binary categories of 'close' and 'not close'; we demonstrate that they did not justify or address the implications of this choice, did not have sufficient statistical power for their approach, and moreover show that slightly adjusting their definition of 'close' would reverse their conclusions. We then present a new analysis of the original dataset, measuring directly the extent to which drivers changed their behaviour in response to helmet wearing. This analysis confirms that drivers did, overall, get closer when the rider wore a helmet. The distribution of overtaking events shifted just over one-fifth of a standard deviation closer to the rider – a potentially important behaviour if, as theoretical frameworks suggest, near-misses and collisions lie on a continuum. The paper ends by considering wider issues surrounding this topic and suggests public health research might be best served by shifting focus to risk elimination rather than harm mitigation.